2017
DOI: 10.5901/mjss.2017.v8n1p463
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Self-regulation: An Associational Study on High School Students in Iran

Abstract: Self

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Los Estilos de Aprendizaje han sido identificados como fuentes relevantes de información para el desarrollo de conocimientos metacognitivos (Safari y Hejazi, 2017), en tanto éstos se relacionan con el desarrollo de habilidades para el aprendizaje autorregulado y autónomo, Versión en línea. Artículo/Article el cual, a su vez, ha sido identificado como un fuerte predictor para el éxito de los procesos de aprendizaje (Veenman et al, 2006).…”
Section: Metacognición Y Aprendizaje Autorreguladounclassified
“…Los Estilos de Aprendizaje han sido identificados como fuentes relevantes de información para el desarrollo de conocimientos metacognitivos (Safari y Hejazi, 2017), en tanto éstos se relacionan con el desarrollo de habilidades para el aprendizaje autorregulado y autónomo, Versión en línea. Artículo/Article el cual, a su vez, ha sido identificado como un fuerte predictor para el éxito de los procesos de aprendizaje (Veenman et al, 2006).…”
Section: Metacognición Y Aprendizaje Autorreguladounclassified
“…In general, the activities in the learning processes are considered as mediators between students, contexts, and achievement within SRL strategies (Pintrich, 2004). Safari and Hejazi (2017) argued that self-regulated learners can get advantage of their own learning because they know how to apply the acceptable actions in order to reach the goals. In the educational context; SRL strategies are seen in the dimensions of self-evaluation, organization, and transformation; goal setting and planning; seeking information, keeping records, and monitoring; environment structuring; self-consequences; rehearsing and memorizing; seeking social assistance; and reviewing records are used (Pintrich and DeGroot, 1990;Schunk and Zimmerman, 1998;Zimmerman, 2002;Zimmerman and Martinez-Pons, 1990).…”
Section: Self-regulation In Programmingmentioning
confidence: 99%
“…For instance, Alharbi et al (2011) reported that some of the students in computer science programs are not aware of their SRL, and that they do not know how to apply SRL strategies in the learning process. Some other studies indicated that students with different learning styles prefer to use different SRL strategies (Shannon, 2008) and stating a relationship between SRL and learning styles may promote learning on the part of students (Safari and Hejazi, 2017). It can be considered that in the process of learning programming, students with different learning styles may follow or develop different self-regulation strategies.…”
Section: Learning Styles In Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…These transitions also show that a single modal representation cannot be sufficient to represent some information or situations (Lemke, 1998). Also, the positive changes in the learning of students who prefer a method suitable for different learning styles (Safari & Hejazi, 2017) feature a detailed examination of the representation types used in coding teaching. The literature review has not yielded any positive result regarding which representations should be used in each step of the coding teaching process (Skiena, 2020).…”
Section: Introductionmentioning
confidence: 99%